(untitled) (Forum Penelitian Agro Ekonomi, 2016)
In the globalization context the perspective contribution and redefinition of agricultural sector are changing. The multifunctional roles and inclusiveness of agriculture become stronger with their ultimate goals as a source of growth and employment, food security enhancement and poverty alleviation, as well as sustaining natural resources and agricultural development. Two fundamental global trends to take into account are inter-temporal strategic environment and anticipative agricultural R&D for development. Global strategic environment consists of biofuel development, climate change, sustainable agriculture, gender mainstreaming, and food-fuel-financial crises. On the other hand, the anticipative agricultural R&D global to get more attention is international trade transparency, technology role and food demand, incentive and investment reformation, structural transformation, and the harmonization of food security and food sovereignty development. Both aspects should be adapted and synergized in the thematic program planning and priority setting of agricultural research for development. The end target is the relevancy and effectiveness of agricultural research and achievement of agricultural development.